2015
DOI: 10.3390/chromatography2020277
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Biochemical Screening Methods for Volatile and Unstable Sesquiterpenoids Using HS-SPME-GC-MS

Abstract: HS-SPME-GC-MS has been suggested as a fast and robust analytical platform for the product characterization of sesquiterpene synthases. The choice of fiber and injection temperature can have a significant effect on the observed product profile, due to the chemical rearrangements that can occur on the fiber material. Here we present a systematic study on the effects of fiber choice and injection port temperature on the observed sesquiterpenoid profile of four sesquiterpene synthases expressed in Nicotiana bentha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 34 publications
1
27
0
1
Order By: Relevance
“…These detection patterns may reflect a volatile nature of 1, 2 and a less volatile nature 5 at 60°C (temperature used during fiber exposure). Our results highlight the importance of using complementary methods to reveal metabolites with different volatility and further supports the use of HS-SPME as a valuable tool for discovery and characterisation of volatile metabolites [16,17]. A lack of head-space sampling in former studies of PpCPS/KS may explain why 1, 2 have not previously been found [5,6].…”
Section: Resultssupporting
confidence: 61%
See 4 more Smart Citations
“…These detection patterns may reflect a volatile nature of 1, 2 and a less volatile nature 5 at 60°C (temperature used during fiber exposure). Our results highlight the importance of using complementary methods to reveal metabolites with different volatility and further supports the use of HS-SPME as a valuable tool for discovery and characterisation of volatile metabolites [16,17]. A lack of head-space sampling in former studies of PpCPS/KS may explain why 1, 2 have not previously been found [5,6].…”
Section: Resultssupporting
confidence: 61%
“…Further supporting that non-enzymatic conversion of terpenoids can occur, a recent study has demonstrated instability of another hydroxylated terpene synthase product [17]. More studies are needed to determine whether 3 is a true enzymatic product of PpCPS/KS and what the rate of conversion of 5 to 3 is.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations